The Composition of Long Line During The Before Night and After Night In The Kelurahan Langgam Kecamatan Langgam District Pelalawan - Joni Irawan; Bustari '; Pareng Rengi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This research was conducted on 21 to 27 november 2015, in the kelurahan langgam kecamatan langgam kabupaten pelalawan. the porpose of this study was to determine the differences in the composition of long line during the before night and last night.The research used a survey method. The operation of long line fishing gear held on over 7 days.The long line catches consist ot 4 spescies, either in the before night and last night with the weight was 15,8 kg at before night (19 fishes) and last night 23,3 kg (26 fishes). The species of fish which were caught consist of Selais (Cryptopterus bichirchis), Juaro (Pangasius polyurandon), Patin (Pangasius pangasius), Baung (Mystus nemurus).Keyword : long line. After night, before night